2016
DOI: 10.1016/j.envres.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and priorities for modelling livestock health and pathogens in the context of climate change

Abstract: Climate change has the potential to impair livestock health, with consequences for animal welfare, productivity, greenhouse gas emissions, and human livelihoods and health. Modelling has an important role in assessing the impacts of climate change on livestock systems and the efficacy of potential adaptation strategies, to support decision making for more efficient, resilient and sustainable production. However, a coherent set of challenges and research priorities for modelling livestock health and pathogens u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 128 publications
0
23
0
1
Order By: Relevance
“…The indirect effects on livestock come through impacts on fodder quantity and quality and pests and disease. The most important direct effects of climate change on animals would be thermal stress (cold and heat) and water availability, while the major indirect effects are expected to be from livestock diseases [7,78].…”
Section: Impact Of Climate Change On Livestock Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect effects on livestock come through impacts on fodder quantity and quality and pests and disease. The most important direct effects of climate change on animals would be thermal stress (cold and heat) and water availability, while the major indirect effects are expected to be from livestock diseases [7,78].…”
Section: Impact Of Climate Change On Livestock Industriesmentioning
confidence: 99%
“…To cope with reductions in the length of growing season and NPP (e.g., in Australia), the risk of soil erosion should be considered and controlled in the adaptations adjusting ground cover threshold, particularly in relation to grazing intensity [10]. Further research is required to focus on impact of climate change on animal diseases, and welfare generally, as previously there are a limited number of previous studies [78,84].…”
Section: Livestockmentioning
confidence: 99%
“…Numerous evidences prove that the climate is changing with effects on human life and activities. Animal agriculture systems are needed to supply food but they are likely to be affected by climate, through an indirect effect on feed production ( € Ozkan et al 2016) and a direct impact on animal welfare, production and reproduction (Bernabucci et al 2010). The increase of temperature, the concentration of pouring rains and the lengthening of droughts are weather features related to climate change that may threaten crops yield and carrying capacity of rangelands in south Europe with the reduction of the suitable areas for traditional agricultural activities (Olesen and Bindi 2002;Nardone et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The main direct impacts reported include reduced immunity to infections (e.g., due to heat stress), increased development rates of pathogens, and prevalence of infectious diseases during extreme weather events [6,57]. Indirect impacts are attributed to variations in temperature and rainfall, which included increase in persistence and abundance of disease vectors and parasites, host resistance to infectious agents, and changes in the severity of human-livestock diseases [41,58]. Moreover, several authors identified extreme examples of climate driven livestock diseases, such as ruminants' helminthological infections [42] (e.g., nematode infections in cattle [43]), avian influenza [59], higher clinical mastitis incidence in dairy cows [60], and parasitic diseases (e.g., movement of tick-borne infestations [61]).…”
Section: Climate Change Impacts On Livestockmentioning
confidence: 99%